The effectiveness of training and development at Suruhanjaya Syarikat Malaysia (SSM) headquarters / Nur Hashima Zahari - Zahari, Nur Hashima (Faculty of Business and Management, 2019)
Every organization wants to achieve their goals and the most important things are their organizational performances .The organizational performances will affect whether the organization achieve their aim or not. Every organization will do the training and development to ensure their employees increase their performances before to achieve the good organizational performances. In this research it will shown on how effective the training and development academy at Suruhanjaya Syarikat Malaysia (SSM) headquaters. The independent variable is Training and development with the component (Training design ,delivery style and On- The job training ) . The dependent variable is organizational performances. The objective of this study is to know the effectiveness of training and development at Suruhanjaya Syarikat Malaysia (SSM).A quantitative research had been done that been adopted using multiple choice question and Likert-scale questionnaire. The questionnaire been distribute to the employees of Suruhanjaya Syarikat Malaysia (SSM) Headquarters at Menara SSM@Sentral . The data collection was collected by this research and analyzed by SPSS. The result analyzed the frequency output, realibility analysis, pearson correlation analysis and multiple regression. From the result, it shows that there is a relationship between the independent variables and the dependent variable.